The cost of love: financial consequences of insecure attachment in antisocial youth. (8th September 2019) - Bachmann, Christian J.; Beecham, Jennifer; O'Connor, Thomas G.; Scott, Adam; Briskman, Jackie; Scott, Stephen
Abstract : Background: Knowing that your parent or caregiver will be there for you in times of emotional need and distress is a core aspect of the human experience of feeling loved and being securely attached. In contrast, an insecure attachment pattern is found in many antisocial youth and is related to less sensitive caregiving. Such youth are often distrustful of adults and authority figures, and are at high risk of poor outcomes. As they become adults, they require extensive health, social and economic support, costing society ten times more than their well‐adjusted peers. However, it is not known whether insecure attachment itself is associated with higher costs in at‐risk youth, independently of potential confounders, nor whether cost differences are already beginning to emerge early in adolescence. Methods: Sample : A total of 174 young people followed up aged 9–17 years (mean 12.1, SD 1.8): 85 recruited with moderate antisocial behaviour (80th percentile) from a school screen aged 4–6 years; 89 clinically referred with very high antisocial behaviour (98th percentile) aged 3–7 years. Measures : Costs by detailed health economic and service‐use interview; attachment security to mother and father from interview; diagnostic interviews for oppositional and conduct problems; self‐reported delinquent behaviour. Results: Costs were greater for youth insecurely attached to their mothers (secure £6, 743, insecure £10, 199, p  = .001) and more so to fathers (secure £1, 353, insecure £13, 978, p  < .001). These differences remained significant (mother p  = .019, father p  < .001) after adjusting for confounders, notably family income and education, intelligence and antisocial behaviour severity. Conclusions: Attachment insecurity is a significant predictor of public cost in at‐risk youth, even after accounting for covariates. Since adolescent attachment security is influenced by caregiving quality earlier in childhood, these findings add support to the public health case for early parenting interventions to improve child outcomes and reduce the financial burden on society. Abstract : Read the Commentary on this article at doi: 10.1111/jcpp.13111